MATERNAL AGE AND CONSANGUINITY AS RISK FACTORS FOR MENTAL RETARDATION AMONG CHILDREN IN SOUTH JORDAN - Omar Ali Nafi; Awni Mueen Shaheen (European Scientific Journal, ESJ, 2013)
The incidence of childhood mental retardation (MR) remains an alarming situation in South Jordan. The current retrospective study was designed to determine whether consanguinity and maternity age are major risk factors to educate the population and define intervention methods. A total of 108 children diagnosed with MR of unknown etiology were included in this study. Systemic neurological examination and Stanford Binet Intelligence test was conducted for each participant. Overall prevalence of consanguinity was 54.6%, and 75.9% of mothers were less than 30 years old. Consanguinity and mother’s age does not predict mental retardation of unknown etiology Though the finding of our study is concurrent with the published studies, there is no report from South Jordan. It is important to monitor if there is any impact on consanguinity due to social change. We also believe that findings of this study will be useful in creating awareness and thereby educating people of the genetic deformities associated with consanguinity.